Esteem, equivalence and valuation of essential occupations - Tiemann, Michael [Verfasser]; Udelhofen, Stefan [Verfasser]; Fournier, Lisa [Verfasser] (My University, 2023)
"Societal debates on occupations in essential work within the context of the pandemic have fuelled questions relating to the value and appreciation of occupational tasks beyond economic criteria. We compare two lists of essential occupations in order to describe their valuation on the basis of characteristics such as wages, prestige and workload together with an analysis of the qualification levels of employees in these occupations. Our aim is to widen the perspective on the equivalence of general and vocational education by addressing the question as to whether burdens or responsibilities are distributed evenly across workers at all qualification levels in times of crisis. The 2018 BIBB/BAuA Employment Survey serves as our database." (authors' abstract; BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; 370; systemrelevanter Beruf; Gesundheitsberuf; Bildungspersonal; Logistikberuf; Gleichwertigkeit; Wertschätzung; Sozialprestige; Lohn; Qualifikationsniveau; Anforderungsprofil; BIBB/BAuA-Erwerbstätigenbefragung; Regressionsanalyse